POSITIVE VALUES REFLECTED IN THE FILM PLAYED BY FIN ARGUS ENTITLED “CLOUDS” - Mustikawati, Yunitari; Sarmin, Nur Adhariana (Journal of English Literature and Linguistic Studies, 2024)
This study is entitled Positive Values Reflected in the Film Played by Fin Argus Entitled “Clouds”. Film is a medium that has a significant impact on presenting information and as a tool for communicating dispatches to cult or the general public. The purpose of this disquisition is to examine the positive values in the film "Clouds" using Gordon Allport's (1961) theory. This study is concentrated on two exploration problem, the first is what are the types of positive values reflected in the film played by Fin Argus entitled “Clouds” and the second is how the main character demonstrates positive values in the film. The disquisition system used in this study is descriptive qualitative system. The results of this study, the film "Clouds" contains a variety type of positive values, including theoretical values (2 extracts), social values (9 extracts), economics values (3 extracts), aesthetic values (3 extracts), personal values (6 extracts), and religious values (1 extract). The researcher also discovered several necessary values that may be used to gain the terminal values. For case, determination, perseverance, empathy, tone- confidence, open- mindedness, affection, rigidity, dedication, curiosity, honesty, cooperation, tone- care, hard work, humanity, and tone- acceptance. The main character also demonstrates positive values in general throughout the film, for case, in the data there are perseverance (2 extracts), Love and friendship (1 extract), courage (1 extract), authenticity (1 extract), kindness & empathy and positivity & optimism (1 extract).